Total phenolic content and the antioxidant activity of clinacanthus nutans extract - Mat Jusoh, Hanapi; Haron, Normah; Zailani, Nurul Syamimi (2019)
Introduction: Clinacanthus nutans is used as natural nutraceuticals for prevention and treatment of cancer. The purpose of this study is to (i) determine the total phenolic content and antioxidant scavenging capacities of C. nutans in free and bound phenolic acid and (ii) study the relationship between TPC and antioxidant scavenging capacities of C. nutans. Methods: The total phenolic contents were measured using Folin-Ciocalteu assay. Free and bound phenolic were examined by using spectrophotometer while antioxidant capacity were evaluated using DPPH (2, 2-diphenyl-1-picrylhydrazyl) scavenging activity assay. Results: Insoluble phenolic acids showed the highest amount of total phenolic content in C. nutans extracts (6.09+ 0.45 mg gallic acid equivalent (GAE)/ g DW) and exhibited highest antioxidant activity (73.3+0.82 %) as compared to free and soluble phenolic extracts. The IC50 values for free phenolic, soluble bound and insoluble bound phenolic extracts were 0.69+0.02 mg/mL, 0.64+0.04 and 0.60+0.006 mg/mL, respectively. There were positive correlation between insoluble bound phenolic content of C. nutans extracts with antioxidant radical scavenging capacity (R² = 0.893). Conclusions: These results indicate that different phenolic acid forms affect the total phenolic content and antioxidant properties. Natural compounds such as phenolics from C. nutans could be a good source of antioxidant.